(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
We all have right to live free from violence and discrimination to enjoy the highest attainablestandard of physical and mental health to take education, to own property, to vote and to earn. But stillwomen face discrimination on the basis of sex and gender. Domestic violence, sexual violence, lower pay,lack of access to education and job, inadequate health care are prevalent in Indian society. Despiteprogress toward gender equality over last century, women continue to face harassment, abuse, anddiscrimination at work and at home. According to the National Crime Statistics Bureau, anti-social actsagainst women such as dowry, sexual harassment, and other fatalities are constantly increasing.The purpose of this research was to review the need of awareness among women folk regarding theconstitutional provisions specially made for their betterment.